Direct observation of anharmonic coupling in the time domain with femtosecond stimulated Raman scattering. - Kukura, P; Frontiera, R; Mathies, R (2006)
Off-resonant impulsive Raman excitation is used to initiate nonstationary nuclear motion in low-frequency vibrational modes of deuterio-chloroform. Femtosecond time-resolved stimulated Raman probing of the high-frequency C-D stretch reveals additional vibrational sidebands that arise as a result of anharmonic coupling between the impulsively excited low-frequency and the probed high-frequency vibrations. These experiments illustrate the detailed molecular information on anharmonic and reactive surfaces available from multidimensional femtosecond stimulated Raman techniques.